Implementation of Technical Innovation as a Corporate Strategy in DEWA – Power Generation Division processes - ALSAIDI, ABDULRAHMAN SULAIMAN (2017)
The purpose of this paper is to map out how an organization can translates innovation into business value. The organization that was chosen for the study is the Dubai Electricity and Water Authority. DEWA is one of the notable organizations when considering how it has used innovation as a part of its corporate strategic planning to become one of the most efficient organizations. DEWA is one of the few government organizations that have been appreciated for excellent service delivery. When considering how DEWA became innovative company, it is necessary to examine the details of the organization's strategy and the guidelines that it uses to become as innovative entity. In this study, the primary focus is to establish a background on what is innovation as concept, examining particularly innovation management, and covering many aspects for both innovation and innovation management. Subsequently, how innovation is practiced and implemented within DEWA, with a specific focus on the Power Generation Division where many patents have been submitted so far. The findings indicate that the innovative ideas at DEWA are evaluated systematically with the goal of ensuring that they are aligned with the goals and objectives of the organization strategy, the Dubai, the UAE, and the global innovation index. Aligning the ideas with all these guidelines ensures that the organization is continuously moving in the right direction. However, internally it was noted that the Power Generation Division would need some improvements, especially concerning communication, motivation and awareness creation among its employees with regards to innovation.